Improving the performance of hierarchical bandwidth allocation for upstream EPON - Sadon S.Kh.; Din N.Md.; Al-Mansoori M.H.; Yaacob M.B.; Radzi N.A.M.; Mustafa I.S.; Majid M.S.B.A. (2023)
Many issues of intra- optical network unit (ONU) bandwidth allocation in Ethernet Passive Optical Network (EPON) remain open. In this paper, we report the performance of hierarchical bandwidth allocation algorithm incorporated Russian Doll Model (RDM) as a solution to allocate bandwidth for intra- ONU in upstream EPON. The allocation of bandwidth is based on the class of service and its priority. Results confirm significant performance improvements for a wide range of traffic loads and triple-play (video, voice, and data) services in terms of the bandwidth utilization, wasted bandwidth and fairness compared with the SHDBA algorithm. The RDDBA maximum significant performance improvements compared to SHDBA is up to 30% depending on the variant and the characteristics of the network traffic. The hierarchical bandwidth allocation with RDM improves the performance of EPON by satisfying the requests of all ONUs and provide differentiated services by guaranteeing both the priority and fairness. 2010 IEEE.